If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5(3x + 2) = 27 Reorder the terms: 5(2 + 3x) = 27 (2 * 5 + 3x * 5) = 27 (10 + 15x) = 27 Solving 10 + 15x = 27 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-10' to each side of the equation. 10 + -10 + 15x = 27 + -10 Combine like terms: 10 + -10 = 0 0 + 15x = 27 + -10 15x = 27 + -10 Combine like terms: 27 + -10 = 17 15x = 17 Divide each side by '15'. x = 1.133333333 Simplifying x = 1.133333333
| y=7(2)-3 | | (2x-96)= | | 9+10z-1=9z+50-5z | | 3(5)-2y=-5 | | 3(-1)-2y=-5 | | 4x+4=8x-12 | | 52.0g/10.5cm^3 | | 3(-7)-2y=-5 | | 150=3.14r^2 | | 4x-6+7x+1=-3x-4 | | 3(3)-2y=-5 | | (3x+11)= | | 4.2x+34.4x=7.0-9.5x | | 8x+8=6-(2x-6) | | -2/3w=60/1 | | (x+89)= | | 5(x-1)-2x=1 | | y=2(-5)-1 | | x-3/8+2/5=4/5x | | 3ln(x+7)=-3 | | 5x^2+x=-9 | | x=w/10y | | 1/6-x=-2x-1/6 | | 8=4/X | | 36π=4/3πr^3 | | 4/9x1/4 | | 4/9*1/4 | | 9z^2+11=12z | | X^7+2X^5+5X^3=0 | | 2/3*2/3= | | (5x^3-4x)/(7x^3-2) | | 5x+-10=-15 |